PERAN RASIO CAMEL DALAM MEMPREDIKSI PROFITABILITAS PERBANKAN SYARIAH MASA DEPAN - Esti P., RA. Ida Wahyu; Riduwan, Akhmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
The research is aimed to examine (a) the influence of the CAR (Capital Adequency Ratio) to the ROA inthe future, (b) the influence of the NPF ratio (Non Performing Finance) to the ROA in the future, (c) the influenceof the NPM ratio (Net Profit Margin) to the ROA in the future, (d) the influence of BOPO ratio (Operating CostOperational Income) to the ROA in the future, (e) the influence of the FDR ratio (Finance to Deposit Ratio) to theROA in the future. The financial ratio data which can be given is the Syariah Banking statistics from BankIndonesia which is the aggregate or overall in 2005-2015 periods. The analysis method has been carried out byusing multiple linear regression. The result of the research shows that (a) Capital Adequacy Ratio, Non PerformingFinance, Operating Cost and Operational Income, and Finance to Debt Ratio do not have any influence to theReturn on Asset in the future. This is caused by the Sharia Bank is encountered to high operating cost. Meanwhile,the Net Profit Margin has positive influence to the Return on Asset in the future because the managementperformance of a bank has great influence to the profitability in the future, (b) CAMEL ratio can be used to predictthe profitability in the future.Keywords : Capital adequacy ratio, non performing finance, net profit margin, operating cost and operatingincome, and return on assets in the future